KESESUAIAN HIDROGRAF SATUAN SINTETIK TERHADAP HIDROGRAF SATUAN TERUKUR(STUDI KASUS SUB SUB DAERAH ALIRAN SUNGAI PEDINDANG BAGIAN TENGAH) - Gustama Gustama; Fadillah Sabri; Donny Fransiskus Manalu (Jurusan Teknik Sipil Universitas Bangka Belitung, 2018)
A widely used method for analyzing river flow for flood forecasts is hydrograph unit. The hydrograph unit is a direct runoff hydrograph that can be created when there are AWLR record data, debit measurements and rainfall data. Synthetic Unit Hydrograph (SUH) is a unit hydrograph derived based on river data in the same watershed or nearby watershed but has the same characteristics, ie HSS Gama I, HSS Nakayasu, Limasan HSS, HSS Snyder and HSS SCS. Of the two hydrographs, there will be suitability of the hydrograph form that is going to be made. Sub territory of Pedindang River Basin has four flood incidents, namely, date 23-24 February 2016; March 2-3, 2016; March 3-4, 2016; and date 5-6 March 2016. In the analysis of each flood event, the peak discharge of synthetic unit hydrograph is very different from the peak discharge of the measured unit hydrograph. The average peak discharge of synthetic unit hydrograph occurs in the range of 2 or 3 hours, while the measured unit hydrograph of Pedindang River occurs in the range of 7 or 8 hours. In four flood events it is stated that, HSS Gama I approaches RMSE value (validation <10%) to HST form of Pedindang River with value: RMSE incidence I (23,601%); RMSE incidence II (16.315%); RMSE incidence III (50,400%); RMSE incidence IV (22.322%). With this result, it is stated that there is no synthetic unit hydrograph model that has compatibility with the measured unit hydrograph of Pedindang River.